The influence of product quality and price on customers' decision to switch from IndiHome - Ardana, Yudhistira (PHINISI, 2025)
Brand switching behavior in the telecommunications industry, particularly among IndiHome customers, is often influenced by factors such as product quality and price. This research aims to examine the impact of product quality and price on customers' decisions to switch brands. The method used is an explanatory quantitative approach, with data collected through questionnaires from 45 respondents who have experienced switching from IndiHome to another service provider. The results indicate that product quality has a positive and significant effect on brand switching behavior. Conversely, price does not show a significant effect on the decision to switch brands. This model is able to explain 38.9% of the variance in switching behavior, suggesting that there are other factors, such as service quality and customer experience, that also play important roles. Theoretically, these findings contribute to consumer behavior literature by affirming that perceptions of product quality have a more dominant influence than price in shaping switching intentions, particularly in the context of subscription-based services like telecommunications. Managerially, the implications of this research indicate that telecommunications companies should prioritize continuous improvement of product and service quality to reduce the risk of customer loss. Although price was not found to have a significant effect, maintaining price competitiveness remains important in facing the intense competition in the industry.